2012
DOI: 10.3758/s13423-012-0329-4
|View full text |Cite
|
Sign up to set email alerts
|

Decisional separability, model identification, and statistical inference in the general recognition theory framework

Abstract: Recent work in the general recognition theory (GRT) framework indicates that there are serious problems with some of the inferential machinery designed to detect perceptual and decisional interactions in multidimensional identification and categorization (Mack, Richler, Gauthier, & Palmeri, 2011). These problems are more extensive than previously recognized, as we show through new analytic and simulation-based results indicating that failure of decisional separability is not identifiable in the Gaussian GRT mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 28 publications
2
97
0
Order By: Relevance
“…1 GRT-wIND solves a number of problems that have been recently identified in traditional GRT models. Importantly, while traditional GRT models have problems dissociating perceptual and decisional forms of separability in the 2 Â 2 identification design (e.g., Mack, Richler, Gauthier, & Palmeri, 2011;Silbert & Thomas, 2013), we have shown that GRT-wIND does not suffer from these problems (see appendix of Soto et al, 2015).…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…1 GRT-wIND solves a number of problems that have been recently identified in traditional GRT models. Importantly, while traditional GRT models have problems dissociating perceptual and decisional forms of separability in the 2 Â 2 identification design (e.g., Mack, Richler, Gauthier, & Palmeri, 2011;Silbert & Thomas, 2013), we have shown that GRT-wIND does not suffer from these problems (see appendix of Soto et al, 2015).…”
Section: Methodsmentioning
confidence: 95%
“…Recent work (Mack et al, 2011;Silbert & Thomas, 2013) has shown that decisional separability is not identifiable in traditional GRT models for the 2 Â 2 identification design. In some cases, perceptual separability might also show identifiability problems.…”
Section: Identifiability Issues In Grt-windmentioning
confidence: 98%
See 2 more Smart Citations
“…Although this may seem to be a very strong assumption, in the standard 2 × 2 GRT model (i.e., the model of stimuli defined by the factorial combination of two levels on each of two dimensions), deviations from this assumption are not identifiable (Silbert and Thomas 2013); it is useful to think of the decision bounds as both partitioning the perceptual space into response regions and (implicitly) defining the axes of the perceptual space. Figure 1 shows four illustrative 2 × 2 Gaussian GRT models, each defined with respect to the stops [p], [b], [t], and [d], which consist of the factorial combination of place of articulation (labial vs. alveolar) and voicing (voiced vs. voiceless).…”
Section: The Structure Of General Recognition Theorymentioning
confidence: 99%